IOT BASED DATA ACQUISITION FOR TERRACE GARDENING - Dr. M. Dhinakaran; Prof. P. Deepthi; Prof. R. Yoganapriya (International Conference on Multidisciplinary Research Perspective, 2025)
The Internet of Things is used in current age of creative computing and it’s providing opportunities to communicate around the world. IoT describes a system where items in the real world, and also sensors within or attached to these items, are connected to the Internet via wireless and wired connections. M2M communications and intelligence drawn from the devices and therefore the network can enable businesses to alter bound basic tasks while not looking at central or cloud-based applications and services. The Aim of this paper is to monitor the environment of the plants in terrace garden. This can be done by measuring parameters such as temperature, humidity, soil moisture and light intensity of the garden. Here in this paper, the data of these parameters are collected and viewed in the form of graph by using thing speak website (online platform, in which data is represented graphically). The data displayed as an output can be observed and forecasted. Now a day’s terrace gardening is developing in cities. The terrace garden is helpful for a family to meetup at least some of the vegetable needs. Thus, this project is used for monitoring environmental data of the plants in order to improve the effectiveness of terrace gardening.